2010
DOI: 10.1007/s00464-010-1331-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hemostatic properties between collagen and synthetic buttress materials used in staple line reinforcement in a swine splenic hemorrhage model

Abstract: The intrinsic hemostatic properties of different buttressing materials vary widely. In this study, a collagen buttress was significantly better at promoting hemostasis than the synthetic buttress material in a nonstapling model. This could be another factor to consider when choosing a buttress for staple line reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The hemostatic mechanism of the sponges might have consisted of three aspects. First, Col induced platelet aggregation, the coagulation factor, and thrombin generation . Second, Ch quickly bonded to the red blood cells, and this resulted in a cellular hemostatic plug and the acceleration of local clot formation.…”
Section: Resultsmentioning
confidence: 99%
“…The hemostatic mechanism of the sponges might have consisted of three aspects. First, Col induced platelet aggregation, the coagulation factor, and thrombin generation . Second, Ch quickly bonded to the red blood cells, and this resulted in a cellular hemostatic plug and the acceleration of local clot formation.…”
Section: Resultsmentioning
confidence: 99%
“…The better results demonstrated with bovine pericardium over an absorbable buttress may be solely due to its increased thickness (1 vs. 0.5 mm). However, in a hemostasis animal model, Spector et al [ 48 ] reported that a collagen matrix biologic buttress was superior to a synthetic buttress for promoting hemostasis and in fact performed as well as a conventional hemostasis product.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of hemostatic agents or sponges have been explored, such as light-cured gelatin hydrogel glues, cyanoacrylate adhesives, microcrystalline collagen and collagen sponges, gelatin sponge, fibrin glue [16,17,18]. Unfortunately, each of them has its own shortcomings.…”
Section: Introductionmentioning
confidence: 99%